Uma abordagem baseada em modelos para especificação e detecção de situações em sistemas sensíveis ao contexto - Mielke, Izon Thomaz (2013)
Context-aware applications manipulate context information to adapt services according to the users current situation and needs. One of the challenges of developing context-aware applications refers to the specification of the conceptual models that represent the situations of interest. The objective of this thesis is to propose a model-driven methodology to assist the development of context-aware applications, focusing on the specification and the detection of contextual situations. To achieve this goal, the work proposes a graphical language for modeling situations, coined SML (Situation Modeling Language), which allows the user to specify situation types considering aspects such as composition of situations and their temporal reasoning. In order to allow situation detection, the models described in SML can be used to generate a rule-based implementation, which is capable of observing context and controlling situations lifecycle. The work describes how the elements specified in SML are transformed into code to be executed in the Drools rule engine. Finally, to support the development of applications, we propose tools to assist the modeling phase, as well as the implementation phase, by means of code generation. The concepts involved in the design of SML and the transformations of SML models to Drools code are exemplified by means of a banking scenario for detecting fraudsusceptible behavior.